TO STUDY THE EFFICACY OF YASHTIMADHU KWATH AASHCHONTANA IN SIMPLE HYPERAEMIA OF CONJUNCTIVA WSR SIROTPATA (AYUSHDHARA, 2018)
This is a study of Effect of Yashtimadhu kwath Aashchontana in simple Hyperaemia of Conjunctiva (Sirotpata). Simple Hyperaemia of conjunctiva means congestion of the conjunctival vessels without being associated with any of the established disease. Aachrya Sushruta describeSirotpata Netra-vikar in Uttartantra. In Sirotpata eyes becomes reddish “tamra with or without pain”. According Aacharya Vagbhatta, in Sirotpata eyes becomes reddish because of conjunctival vessel congestion and Netra daha is also present but there is no pain, watering or mucous discharge. Sushruta described Sirotpata as a Raktavikarjanya – Sadhya vyadhi, so Chikitsa of Sirotpata is described in Raktaabhishandya prathishodhan Aadhyaya. So we can correlate conjunctival hyperaemia with Sirotpata. Yashtimadhu is one of the well known Chakshushya dravya in Ayurveda. Yashtimadhu have Madhur rasa, Madhur vipaka, Snigdha, Guru-guna and Shitviriya so it is good Rakta pitta shamak. In hypermaemia of conjunctiva, Rakta-pitta dushti is present. Yashtimadhu kwath aaschantana help to reduce Vata-pitta dushti. We use Yashtimadhu kwath aashchontana in simple hyperaemia of conjunctiva i.e. Sirothpata. We choose fifteen patients of conjunctival simple hyperaemia to give Yashtimadhu kwath Aashchantana 10 drops per day for 7 days. After 7 days out of 10, in most of the patients conjunctival congestion as well as ocular discomfort decrease. It can be concluded that Yashtimadhu Kwath Aashchontana is useful in conjunctival hyperaemia w.s.r. Sirotpata.